The effect and prioritization of international branding components of the tourism industry in tourism marketing in Tehran - Aghaziarati, Shahla; Samet, Alireza; Seyed Fazli, Hadi (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The purpose of this research was the influence and prioritization of the international branding components of the tourism industry on tourism marketing in Tehran. Method: This study was a descriptive survey in terms of implementation methods. The statistical population included all technical officials and managers of the Institute of International Tourist Companies and tourist tour guides of Tehran province in 2022, numbering 8499 people. Using the table of Krejcie and Morgan and the available method, 367 people were selected as the sample size. The data collection tool was the international tourism branding questionnaires made by the researcher based on Jalalian’s research (2019) and Sangabi’s tourism marketing (2014). The data were analyzed using descriptive statistics (frequency and percentage) and inferential statistics (Kolmogorov Smirnov, t-test and regression) using SPSS-26 software. Results: The results showed that the international branding components of the tourism industry affect tourism marketing in Tehran. Also, the results showed that brand image, awareness, perceived quality, and loyalty are the most important components of the tourism industry’s international branding in Tehran’s tourism marketing. Conclusion: One of the reasons for the importance of the concept of special brand value is that city managers and company owners can gain a competitive advantage with the help of brands with high special value. The more positive the tourists’ evaluation of each of the specific brand value dimensions, the higher the brand of that destination has a higher specific value among tourists.